Effectiveness of Back Massage Therapy to Reduce Acute Pain in Hypertension in the Working Area of Health Center Kading Bone Regency - Mardiana Mardiana (Newinera Publisher, 2021)
Background Background : The World Health Organization (WHO) explained that the prevalence of hypertension in the world amounted to 1.13 billion . The prevalence of hypertension in Indonesia amounted to 8 , 36 % of some provinces in Indonesia. The increasing number of people with hypertension can be caused by several factors , including: environment , behavior , and offspring that can , causing the patient a patient experiencing pain head . Purpose : This study aims to assess the effectiveness of back massage therapy in reducing pain in hypertensive patients . Methods : This study was a Quasy experiment with a pretest-posttest control gro up . A sample of 30 respondents who were divided into 2 groups . Group intervention (n = 15) who received treatment massage the back and the group control received treatment techniques of relaxation breath in (n = 15). Results : analysis of research that is conducted on a group of interventions by using a test of independent samples t-test showed a value significantly decrease scale of pain in patients with hypertension with a value of p = 0.000 , while the group of control showed the value of p = 0.082 by administration of therapeutic relaxation breath in . CONCLUSIONS in research is massage the back of effectively lowering of pain in patients with hypertension.